Chimera states with multiple coexisting solutions - Gui-Quan Sun; Zhi-Chao Xue; Li Li; Jing Li; Charo I. del Genio; Stefano Boccaletti (Physical Review Research)
We report on the emergence of chimera states in extended systems characterized by the coexistence of more than two spatiotemporal solutions. Specifically, we show that three-domain chimeras may generically appear in reaction-diffusion systems under three conditions, with a crucial role played by the existence of a Maxwell point. We verify the universality of our findings by analyzing five different models, and demonstrate that such new chimeras are independent of the boundary conditions imposed.